Histórias de trabalhadores no processo de transformação das relações capitalistas em Rolim de Moura/RO (1970-2018) - Paula, Cátia Franciele Sanfelice de (2018)
This research discusses the process of changes and transformation in capitalist social relations in Rolim de Moura/RO, between 1970 and 2018. By moving from a structural analysis, from the memories of the workers who migrated in the 1970s and 1980s, we seek to understand how they lived a process of adversity and deprivation marked by conflicts of different nature. We place at the center of the investigation the social relations that were present in a historical and political moment, marked by the civic-military regime, the advance of the borders and the creation of several organs and intervention projects as an attempt to social control by those who took over the executive agencies of the "colonization" projects in Rondônia. Among dreams, projections and expectations that moved workers, we highlight how the limits faced by them, delineated the constitution of collective effort and preclude their permanence in the countryside. As a dynamic and moving process, the relations changed as workers suffered and exerted pressures. In the correlation of forces with different agents, we highlight the worker’s experiences, the political configuration and how the State intervened through public policies that favored the formation of a market economy responsible for changing and modifying ways of living, working and fighting in Rolim de Moura.